RB-GACA: an RBAC based grid access control architecture. (17th May 2005) - Jin, Hai; Qiang, Weizhong; Shi, Xuanhua; Zou, Deqing
Grid computing is emerging as a new format of wide area distributed computing. Because the distribution of services and resources in wide-area networks are heterogeneous, dynamic, and multi-domain, security is a critical concern in grid computing. Authorisation and access control, which are important aspects of security, have obtained more and more attention. This paper proposes a universal, scalable authorisation and access control architecture, RB-GACA, for grid computing. It is based on classical access control mechanism in distributed applications, Role Based Access Control (RBAC). The paper provides a flexible policy management approach for various grid environments. We also use a standard policy language for the presentation of access control policies to provide a general and standard support for different services and resources.